2013
DOI: 10.1177/0956797613498908
|View full text |Cite
|
Sign up to set email alerts
|

When Left Is Not Right

Abstract: According to the body-specificity hypothesis, hearing action words creates body-specific mental simulations of the actions. Handedness should, therefore, affect mental simulations. Given that pictures of actions also evoke mental simulations and often accompany words to be learned, would pictures that mismatch the mental simulation of words negatively affect learning? We investigated effects of pictures with a left-handed, right-handed, or bimanual perspective on left- and right-handers' learning of object-man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…Secondly, because we were able to include multiple experiments in the combined analysis, we had a large sample size, which means that we can be fairly certain that the effect exists, although it is small. Finally, the small effect size is consistent with prior studies using the same materials (De Nooijer, Van Gog, Paas, & Zwaan, 2013;Rop et al, 2016) and may perhaps be due to the relatively low complexity of the learning materials. All things considered, we can regard this replication attempt a modest success, although the effect size for the crucial interaction we found is much smaller than the effect size reported in Rop et al (2016).…”
Section: Limitations and Future Researchsupporting
confidence: 86%
“…Secondly, because we were able to include multiple experiments in the combined analysis, we had a large sample size, which means that we can be fairly certain that the effect exists, although it is small. Finally, the small effect size is consistent with prior studies using the same materials (De Nooijer, Van Gog, Paas, & Zwaan, 2013;Rop et al, 2016) and may perhaps be due to the relatively low complexity of the learning materials. All things considered, we can regard this replication attempt a modest success, although the effect size for the crucial interaction we found is much smaller than the effect size reported in Rop et al (2016).…”
Section: Limitations and Future Researchsupporting
confidence: 86%
“…So, every participant could score a maximum of 6 points on each test. We adopted the scoring scheme of De Nooijer et al (2013) who used the same materials (they found an interrater reliability of κ = .82), but established interrater reliability again for the present study, by having part of the data (10.6 %) scored by a second independent rater. Both raters saw only the definitions and words during scoring, so they were blind to the experimental condition under which each word was learned.…”
Section: Methodsmentioning
confidence: 99%
“…Another study investigated the effects of pictures on action word learning in a 'second' artificial language, which matched or mismatched the learners' handedness (De Nooijer et al, 2013). Participants first saw the artificial language word (e.g.…”
Section: Multimedia and Coherence Effects In Word Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Right-handers could remember more instructions when an object's handle was oriented to the right and actions also had to be performed with the right-hand. Also, research has shown that when learning new words coupled to a picture of a left or a right-handed picture perspective, right-handers recall fewer word definitions, when the picture seen during learning mismatches the right-handed mental simulation evoked by the verbal definition (De Nooijer, Van Gog, Paas, & Zwaan, 2013). Behavioural results can, however, reflect later processes than those reported from ERP data.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%